Optimum long-term planning of a radial primary distribution network: Part II: Development of the optimum long-term planning method - Salis, G.J.; Safigianni, A.S. (International journal of electrical power & energy systems, 1998)
With this second part the paper dealing with the optimum long-term planning of a radial primary power distribution network is completed. In this part an algorithm for this planning is developed, taking into account the locations and the time variation of the load served by the examined network, technoeconomical constraints and functions given in Part I of this paper and previous papers of the authors. This algorithm finally proposes a network form selecting the proper conductors for the network segments and concrete years with the kinds of specific improvements to which this form must be subject inside the specific plan period in order to satisfy the continuous growing load in the technoeconomically best way.